Altered Ex-Vivo Cytokine Responses in Children With Asymptomatic Plasmodium falciparum Infection in Burkina Faso: An Additional Argument to Treat Asymptomatic Malaria? - Post, Annelies; Kaboré, Berenger; Berendsen, Mike; Diallo, Salou; Traore, Ousmane; Arts, Rob J. W.; Netea, Mihai G.; Joosten, Leo A. B.; Tinto, Halidou; Jacobs, Jan; de Mast, Quirijn; van der Ven, André (Frontiers in Immunology, 2021)
Introduction Patients with clinical malaria have an increased risk for bacterial bloodstream infections. We hypothesized that asymptomatic malaria parasitemia increases susceptibility for bacterial infections through an effect on the innate immune system. We measured circulating cytokine levels and ex-vivo cytokine production capacity in asymptomatic malaria and compared with controls. Methods Data were collected from asymptomatic participants <5 years old with and without positive malaria microscopy, as well as from hospitalized patients <5 years old with clinical malaria, bacteremia, or malaria/bacteremia co-infections in a malaria endemic region of Burkina Faso. Circulating cytokines (TNF-α, IFN-γ, IL-6, IL-10) were measured using multiplex assays. Whole blood from asymptomatic participants with and without positive malaria microscopy were ex-vivo stimulated with S. aureus, E. coli LPS and Salmonella Typhimurium; cytokine concentrations (TNF-α, IFN-γ, IL-1β, IL-6, IL-10) were measured on supernatants using ELISA. Results Included were children with clinical malaria (n=118), bacteremia (n=22), malaria and bacteremia co-infection (n=9), asymptomatic malaria (n=125), and asymptomatic controls (n=237). Children with either clinical or asymptomatic malaria had higher plasma cytokine concentrations than controls. Cytokine concentrations correlated positively with malaria parasite density with the strongest correlation for IL-10 in both asymptomatic (r=0.63) and clinical malaria (r=0.53). Patients with bacteremia had lower circulating IL-10, TNF-α and IFN-γ and higher IL-6 concentrations, compared to clinical malaria. Ex-vivo whole blood cytokine production to LPS and S. aureus was significantly lower in asymptomatic malaria compared to controls. Whole blood IFN-γ and IL-10 production in response to Salmonella was also lower in asymptomatic malaria. Interpretation In children with asymptomatic malaria, cytokine responses upon ex-vivo bacterial stimulation are downregulated. Further studies are needed to explore if the suggested impaired innate immune response to bacterial pathogens also translates into impaired control of pathogens such as Salmonella spp.